2020
DOI: 10.1016/j.jpubeco.2020.104260
|View full text |Cite
|
Sign up to set email alerts
|

The macroeconomic effects of lockdown policies

Abstract: A tractable incomplete-market model with endogenous unemployment risk, sticky prices, real wage rigidity and a fiscal side is calibrated to Euro Area countries and used to analyze the macroeconomic effects of lockdown policies. Modeling them as a shock to the extensive margin of labor adjustment – a rise in separations – produces large and persistent negative effects on output, unemployment and welfare, raises precautionary savings and lowers inflation, in line with early evidence about inflation dynamics. Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 36 publications
0
30
0
2
Order By: Relevance
“…While protocols impose an additional layer of costs to firms, they can have benefits for aggregate economic performance since by reducing the risk of contagion they allow employees to go back to work. Hence, firm protocols do not necessarily produce a tradeoff between economic performance and health as often argued in the case of lockdowns ( Auray, Eyquem, 2020 , Alvarez, Argente, Lippi, 2020 , Eichenbaum, Rebelo, Trabandt, 2020 , Kaplan, Moll, Violante, 2020 ). Some studies have even suggested that lockdowns, if one takes a broader view of their impact on health, have had rather negative consequences for aspects of health unrelated to the spread of the virus.…”
Section: Introductionmentioning
confidence: 97%
“…While protocols impose an additional layer of costs to firms, they can have benefits for aggregate economic performance since by reducing the risk of contagion they allow employees to go back to work. Hence, firm protocols do not necessarily produce a tradeoff between economic performance and health as often argued in the case of lockdowns ( Auray, Eyquem, 2020 , Alvarez, Argente, Lippi, 2020 , Eichenbaum, Rebelo, Trabandt, 2020 , Kaplan, Moll, Violante, 2020 ). Some studies have even suggested that lockdowns, if one takes a broader view of their impact on health, have had rather negative consequences for aspects of health unrelated to the spread of the virus.…”
Section: Introductionmentioning
confidence: 97%
“…Large scale lockdowns, however, entail costs including lost revenues for firms, lower productivity, and higher unemployment ( Auray, Eyquem, 2020 , Kong, Prinz, 2020 ). This prompted a heated debate among entrepreneurs, legislators, and the epidemiological expert community ( Wong, 2020 ), with some countries refraining from introducing strict nationwide measures.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, labour forces expected to carry out production (Soylu et al, 2018). Auray & Eyquem (2020) also explained the unemployment rate could be confined or reduced during the COVID-19 via Government's several initiatives, especially with the government-linked companies. Thus, these initiatives generate a large amount of slack in the labour market, which will raise the output and productivity to recover the economy.…”
Section: Determinants Of Economicmentioning
confidence: 99%